NILAI-NILAI RELIGIUS DALAM SASTRA KALINDAQDAQ SUKU MANDAR DAN RELEVANSINYA TERHADAP MATERI AKIDAH AKHLAK DI MADRASAH ALIYAH NEGERI 1 MAJENE - Muhammad Rif'ah; Rahmawati; M. Fauzan Fahmi; Susilo Kamal; ST Muthahharah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study examines the religious values embedded in the Kalindaqdaq oral literature of the Mandar ethnic group and their relevance to the Akidah Akhlak (Faith and Morals) subject matter at Madrasah Aliyah Negeri (MAN) 1 Majene. Using a descriptive qualitative approach through field research, data were collected via observation, interviews with cultural practitioners and Akidah Akhlak teachers, and documentation of Kalindaqdaq texts, then analyzed using the interactive model of Miles and Huberman comprising data reduction, data display, and conclusion drawing. The findings show that Kalindaqdaq is the cultural foundation of Mandar literary and artistic forms, characterized by a fixed four-line structure with an 8-7-5-7 syllabic pattern preserved across generations. The arrival of Islam enriched rather than replaced its identity, infusing it with strong religious content, including tawhid (rububiyah), noble character formation, and spiritual awareness conveyed through figurative language. These values are relevant to the Akidah Akhlak curriculum for Grades X, XI, and XII, particularly regarding self-control, simplicity, justice, filial piety, courteous social conduct, optimism, and the strengthening of tawhid, indicating that Kalindaqdaq has strong potential as a contextual learning resource that engages students' affective understanding of Islamic teachings.